Renal Manifestation of an Adolescent Boy With Bardet- Biedl Syndrome - Akbar, Romana; Jesmin, Tahmina; Roy, Ranjit Ranjan; ALI, ASIF (Journal of Pediatric Nephrology, 2025)
Background and Aim: Bardet-Biedl syndrome (BBS) is a rare autosomal recessive multisystemic genetic disorder that may affect the centrosome and ciliary transport. Retinal dystrophy, obesity, extremity deformities, mental retardation, and renal and genital system anomalies characterize the disease. Renal involvement is a major cause of morbidity and mortality. Case Presentation: We report the case of a 16-year-old boy with BBS who had a history of delayed diagnosis and features of glomerulonephritis leading to chronic kidney disease. He underwent a renal biopsy, which revealed focal segmental glomerulosclerosis (FSGS) from a histopathological study. Conclusion: To our knowledge, only a few FSGS cases have been previously reported in pediatric patients with this syndrome. We wish to alert clinicians to a wide variety of renal abnormalities that can be observed in patients with this rare disorder and to provide multidisciplinary management of BBS.